ASME 2013 7th International Conference on Energy Sustainability 2013
DOI: 10.1115/es2013-18365
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self-Cleaning Solar Collectors for Minimizing Energy Yield Loss Caused by Dust Deposition

Abstract: Concentrated Solar Power (CSP) systems used for photothermal conversion of solar energy to electricity are capable of meeting a large fraction of the global energy requirements. CSP plants are inherently robust with respect to the availability of materials, technology, and energy storage. However, dust depositions on solar collectors cause energy yield loss annually, ranging from 10 to 50% depending upon their location in the semi-arid and desert lands. Mitigation of energy loss requires manual cleaning of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Experiments for numerous trials have shown more than 90% reflectivity restoration is possible after EDS activation on the order of a few minutes [19]. …”
Section: B Manual Cleaningmentioning
confidence: 99%
“…Experiments for numerous trials have shown more than 90% reflectivity restoration is possible after EDS activation on the order of a few minutes [19]. …”
Section: B Manual Cleaningmentioning
confidence: 99%
“…The repulsive forces are first the Coulomb force and then the dielectrophoretic force, which is independent of the particle charge and depends only on the nonhomogeneity of the electric field around the particles. In outdoor operating systems, gravitational and wind force should also be taken into account, which will depend on mounting system and meteorological conditions. During the electrodynamic cleaning process, the dust particles are charged positively by various charge transfer mechanisms such as contact charging when a difference in electronegativity is present between the particles and the surface, tribocharging when particles move over the surface and between each other, and microfilament charging when high space charge is created between the surface and the particles …”
Section: Introductionmentioning
confidence: 99%
“…The electrode design can vary from standard interdigitated electrical line (in particular for standing wave) to spiral design (Figure A). The voltage difference between electrodes usually varies between 0.9 and 7 kV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations